1977
DOI: 10.1017/s0021859600027179
|View full text |Cite
|
Sign up to set email alerts
|

Growth and N-uptake by wheat as affected by sowing date and nitrogen in irrigated semi-arid conditions

Abstract: Field experiments were made under irrigated semi-arid conditions to determine the effects of sowing date and nitrogen application on the growth and yield of wheat and nitrogen-uptake by wheat plants. Early sowing was found to be favourable to high grain production because the post-anthesis period coincided with relatively lower temperatures. Late sowing was unfavourable to grain yields since the period between anthesis and leaf senescence was curtailed by the onset of relatively higher temperature. The benefit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1981
1981
2011
2011

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 16 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…Similar findings were reported by Dubey and Sharma (1996). Khalifa et al (1977) observed that nitrogen uptake was higher during early sowing (1st November) of wheat, which resulted in better leaf expansion, higher leaf area indices and higher leaf area duration. On the other hand, nitrogen uptake was much lower in late sowing (6th December) of wheat, which resulted in decreased leaf expanses, reduced leaf area indices and leaf area duration and thus lower grain production.…”
Section: Harvest Indexmentioning
confidence: 97%
“…Similar findings were reported by Dubey and Sharma (1996). Khalifa et al (1977) observed that nitrogen uptake was higher during early sowing (1st November) of wheat, which resulted in better leaf expansion, higher leaf area indices and higher leaf area duration. On the other hand, nitrogen uptake was much lower in late sowing (6th December) of wheat, which resulted in decreased leaf expanses, reduced leaf area indices and leaf area duration and thus lower grain production.…”
Section: Harvest Indexmentioning
confidence: 97%
“…Yield reductions in latesown wheat is often attributed to inadequate tillering and reduced transpiration late in the season (Doyle and Fischer 1979). High seeding rates can offset much of the adverse effect of late seeding (Khalifa et al, 1977;Doyle and Fischer 1979). For other situations the cause for low yields may be related to occurrence of pests and diseases associated with the sowing date.…”
Section: Improved Crop Agronomymentioning
confidence: 99%